STUDI EKSPLORASI EFEKTIVITAS REVERSE MENTORING TERHADAP PENGUASAAN TEKNOLOGI DI BANK (STUDI KASUS BANK X) - Pramana, Iwan; Kristamuljana, Sammy (Among Makarti, 2024)
Abstract : This study aims to explore the application of Reverse Mentoring to technology mastery in a bank. The study wanted to find out how effective Reverse Mentoring is in helping technology mastery? This is interesting because unlike conventional mentoring, in Reverse Mentoring, the mentoring process is carried out by younger and junior mentors, to older and higher-ranking mentees. In the Reverse Mentoring process, young people are given strategic roles and receive support from the organization to provide mentoring to older people. This study uses a qualitative approach by conducting interviews through purposive sampling. Informants are people involved in the formulation to execution of Reverse Mentoring and users of this program. Thematic analysis was conducted to classify the data obtained. The results showed that Reverse Mentoring is effective in helping technology mastery in the Bank.Abstrak : Studi ini bertujuan untuk mengeksplorasi penerapan Reverse Mentoring terhadap penguasaan teknologi di sebuah bank. Penelitian ingin mengetahui seberapa efektif Reverse Mentoring dalam membantu penguasaan teknologi? Ini menarik karena berbeda dengan mentoring konvensional, dalam Reverse Mentoring, proses  mentoring dilakukan oleh mentor yang lebih muda dan junior, terhadap mentee yang lebih tua serta lebih tinggi secara jabatan. Dalam proses Reverse Mentoring, anak muda diberikan peran strategis dan memperoleh dukungan dari organisasi untuk memberikan mentoring kepada yang lebih tua. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara melalui purposive sampling. Informan adalah orang yang terlibat dalam perumusan hingga eksekusi Reverse Mentoring serta user dari program ini. Analisis tematik dilakukan untuk mengklasifikasikan data yang didapat. Hasilnya, Reverse Mentoring efektif dalam membantu penguasaan teknologi di Bank.